IMPLEMENTATION OF REHABILITATION FOR DRUG ABUSES ACCORDING TO LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS - Bawono, Bambang Tri; Wahyono, Dwi; Laksana, Andri Winjaya (Unissula, 2022)
This study aims to determine and analyze the implementation of rehabilitation for narcotics abusers according to Law no. 35 of 2009 concerning Narcotics and Barriers and what solutions are faced in the implementation of rehabilitation for addicts or narcotics abusers. The approach method used in this research is juridical sociology. The results of this study indicate that the implementation of rehabilitation for addicts or victims of narcotics abuse in principle is carried out through court decisions or requests from addicts or victims of narcotics abusers. There are three stages carried out to return addicts or victims of narcotics abusers to their original state, namely the medical stage, the non-medical stage, and the periodic or advanced stage. The obstacles faced in the implementation of rehabilitation are addicts or victims of narcotics abusers who are already in a semi-crazy condition, addicts or narcotics abusers do not want to open up, family factors, and the view of the police who still apply imprisonment for narcotics addicts.